2003
DOI: 10.1074/jbc.m306903200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Necrosis of H9c2 Myogenic Cells upon Transient Energy Deprivation

Abstract: Subjecting myogenic H9c2 cells to transient energy deprivation leads to a caspase-independent death with typical features of necrosis. Here we show that the rupture of cytoplasmic membrane, the terminal event in necrosis, is shortly preceded by rapid depolarization of mitochondrial membranes. The rapid deenergization of mitochondria critically depended upon prior generation of reactive oxygen species (ROS) during ATP depletion stage. Accordingly, expression of catalase prevented mitochondrial depolarization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Previous work had shown that ARC interacts with caspase 8 to interfere with receptor-mediated death signaling (13) and suppresses potassium efflux through voltage-gated Kv channels (38). ARC has also been shown to block necrosis by preserving mitochondrial integrity (39). Taken together, these results suggest that ARC prevents cell death by interfering with multiple pathways.…”
Section: Fig 3 Co-immunoprecipitation Analysis Of Arc and Baxmentioning
confidence: 56%
“…Previous work had shown that ARC interacts with caspase 8 to interfere with receptor-mediated death signaling (13) and suppresses potassium efflux through voltage-gated Kv channels (38). ARC has also been shown to block necrosis by preserving mitochondrial integrity (39). Taken together, these results suggest that ARC prevents cell death by interfering with multiple pathways.…”
Section: Fig 3 Co-immunoprecipitation Analysis Of Arc and Baxmentioning
confidence: 56%
“…Considering the results that, inhibition of JNK significantly blocked the ∆Ψm loss, mitochondria might be the target of JNK. It is reported that JNK controlled the rapid depolarization of mitochondrial membranes in rotenone-induced H9c2 cells necrosis [43]. In other context, JNK mitochondrial translocation is responsible for mitochondrial dysfunction and eventually the necrotic cell death [44].…”
Section: Discussionmentioning
confidence: 99%
“…Less well understood is the ability of Hsp72 to protect cells from cell death. Hsp72 has been shown to protect cells from necrosis and is capable of protecting and repairing important cell metabolic processes (3)(4)(5)(6). It has also been shown to inhibit apoptosis, whereby cells actively engineer their own destruction in response to extracellular signals and intracellular damage (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%